DETERMINATION OF TOTAL PHENOL CONTENT IN METHANOL EXTRACT OF ROSEMARY (Rosmarinus officinalis L.) LEAVES BY DIGETION METHODS USING UV-VIS SPECTROFOTOMETRY METHODS - Mercyska Suryandari, Mercyska; Dwi Rahayu, Risma; Syafika Rani, Noor (SITAWA : Jurnal Farmasi Sains dan Obat Tradisional, 2024)
The methanol extract of resemary leaves contains terpenoids, alkanoids, flavonoids, tannins, steroids, saponins and polyphenols. The aim of this research was to determine the total phenol of methanol extract of rosemary (Rosmarinus officinalis L.) by digestion method using the UV-Vis spectrophotometric method. In this study, methanol extract of rosemary leaves extracted using the digestion method was used as a sample and gallic acid as a standard. A standard solution of 200 ppm gallic acid was prepared to determine the operating time at 100 minutes and the maximum wavelength at 747 nm. Next, a comparison solution of gallic acid was made with a concentration range of 100, 125, 150, 175, 200 ppm and produced a linear regression equation, namely y = 0.0039× - 0.1146 with a correlation coefficient (r) of 0.9842. Determination of total phenol content was replicated 3 times and the absorption value was observed. The research results showed that the average total phenol content was 57.0317 mgGAE/g extract.